Decreasing Blood Culture Contamination Rates in a Children's Hospital. (4th October 2017) - Chatterjee, Jahnavi; Morgan, Stephanie; Stempak, Lisa; Dowdy, Kristin; Feghaly, Rana El
Abstract: Background: Blood culture contamination is a significant safety and quality issue. It leads to increases in ED visits, admission rates, length of stay, antibiotic use, laboratory tests, and invasive procedures. Our Quality Improvement (QI) project's aim was to reduce the contamination rate in Batson Children's Hospital from 2.76% to <1.5% by December 2017. Methods: A multidisciplinary team was gathered including, nurses, physicians, laboratory directors, infection prevention specialist, an information technology specialist and administration leaders. We built surveys and observation sheets based on a process map and cause-and-effect analysis. Surveys sent to all unit nurses with 399 responses were used to identify problem areas and record most common deviations in the collection process such as collecting blood from old peripheral IVs, not allowing antiseptic solution enough time to dry, re-palpating skin after antiseptic solution is applied. We identified a lack of standardization and education in various units. The volume of blood collected was also low across all units. We standardized the collection protocol, reiterated nurse education via meetings and online modules. Most importantly, we proposed optimal blood volumes based on patients' weight (table) and discussed our recommendations with all nurse managers and educators, and major unit leaders especially oncology and intensive care units. The blood volume chart was piloted in the pediatric emergency department for 4 months. Results: Despite a steady increase in the number of blood cultures collected since 2014, the average contamination rate has decreased from 2.76% to 1.32% (figure), along with an estimated average cost reduction of 58, 690 per month. Conclusion: By standardizing the blood culture collection protocols, optimizing blood volume, creating checklists, and re-enforcing nurse education, we were able to reduce our blood culture contamination to a sustainable low rate. Disclosures: All authors: No reported disclosures.